Blender master class : a hands-on guide to modeling, sculpting, materials, and rendering - Simonds, Ben (No Starch Press, 2013)
Blender is a powerful and free 3D graphics tool used by artists and designers worldwide. But even experienced designers can find it challenging to turn an idea into a polished piece. For those who have struggled to create professional-quality projects in Blender, author Ben Simonds offers this peek inside his studio. You'll learn how to create 3D models as you explore the creative process that he uses to model three example projects: a muscular bat creature, a futuristic robotic spider, and ancient temple ruins. Along the way, you'll master the Blender interface and learn how to create and refine your own models. You'll also learn how to: -Work with reference and concept art in Blender and GIMP to make starting projects easier -Block in models with simple geometry and build up more complex forms -Use Blender's powerful sculpting brushes to create detailed organic models -Paint textures with Blender and GIMP and map them onto your 3D artwork -Light, render, and composite your models to create striking images Each chapter walks you through a piece of the modeling process and offers detailed explanations of the tools and concepts used. Filled with full-color artwork and real-world tips, Blender Master Class gives you the foundation you need to create your own stunning masterpieces. Covers Blender 2.6x.